ECOLOGICAL EFFECTS OF BELIK RIVER HYDRAULIC CHARACTERISTICS ON PERIPHYTON COMMUNITY AS WATER QUALITY BIOINDICATOR - Heni Wahyu Sartika; Suwarno Hadisusanto; Muhammad Sulaiman (SEAMEO BIOTROP, 2024)
ARTICLE HIGLIGHTS- Differences in river hydraulic characteristics affect ecological river health- The influence of flooding on the dynamics of physical and chemical characteristics of river water- Life strategy, adaptation of periphyton to environmental changes- Development of green infrastructure for river conservationABSTRACTBelik River is one of the urban rivers in the Special Region of Yogyakarta which has hydrological problems both in quantity and quality. This triggered the construction of various types of channel modifications. This study aimed to identify water quality and the ecological effects of channel modifications based on the presence of periphyton communities as bioindicators. Sampling was carried out in January 2021 and March 2021. Samples were taken at 4 sampling sites with different channel characteristics with 3 repetitions at each location. The physico-chemical parameters measured included pH, detergent, nitrate, sulfate, total phosphate, TSS, TDS, DO, CO2, water temperature, depth, transparency, discharge, and current velocity. The results showed that the abundance of periphyton in January 2021 was higher than in March 2021. In January 2021 there were found 91 periphyton species dominated by Nitzschia improvisa, Nitzschia terricola, and Nitzschia philippinarum. Meanwhile, in March 2021 there were found 61 species of periphyton dominated by Nitzschia improvisa. Based on the results of Canonical Correlation Analysis (CCA), it was shown that in general the distribution and abundance of periphyton in the Belik River were influenced by CO2, total phosphate, discharge, DO, nitrate, TSS, and depth. The Shannon Wiener Diversity Index showed that water quality in January 2021 has decreased in March 2021. From the cluster analysis, it is known that there are differences in water quality and abundance of periphyton in the four types of river channels. It can be concluded that differences in hydraulic characteristics affected water quality and the ecological health of Belik River.